Systematic comparison between toehold exchange and toehold displacement: exploration for highly specific and sensitive DNA detection. Issue 65 (22nd August 2017) - Yu, Wen; Tang, Lan; Qiu, Ju-Hui; Zhang, Zhang; Zhou, Li-Li; Li, Jun-Long; Xie, Guo-Ming
Abstract : The detection of nucleic acid variations with high specificity and sensitivity is essential for the good practice of precision medicine. Abstract : The detection of nucleic acid variations with high specificity and sensitivity is essential for the good practice of precision medicine. Herein, we explore improving the sensitivity while ensuring the specificity of nucleic acid detection at single base resolution. "Toehold exchange" and "toehold displacement" are the two most widely used strategies in nucleic acid analysis due to their high theoretical specificity. However, to the best of our knowledge, there is no direct comparison between the two strategies to determine which one is more specific for nucleic acid analysis. First, a systematic comparison of the specificity of SNV detection based on toehold exchange and toehold displacement is performed, which shows that toehold exchange exhibits higher discrimination than toehold displacement, both experimentally and theoretically. Second, "plug the reaction", which is a new principle to improve sensitivity without sacrificing specificity is proposed for the first time and demonstrated. This is achieved by adding a "plugging probe" at the equilibrium of toehold exchange. The plugging probe reacts with the product of toehold exchange, thus breaking the equilibrium of the reaction and successfully amplifying the signal. In summary, this work provides universal guidelines for nucleic acid analysis such as the detection of SNVs and rare mutations, which are required for high specificity, and the principle of plug the reaction will present new avenues for sensitive nucleic acid analysis.